Metal-organic frameworks (MOFs) based nanofiber architectures for the removal of heavy metal ions - Heja Ibrahim, Adil; Mohammad R., Thalji; Suhad A., Yasin; Ibtisam A., Saeed; Mohammed A., Assiri; Chong, Kwok Feng; Gomaa A. M., Ali (Royal Society of Chemistry, 2022)
Environmental heavy metal ions (HMIs) accumulate in living organisms and cause various diseases. Metal-organic frameworks (MOFs) have proven to be promising and effective materials for removing heavy metal ions from contaminated water because of their high porosity, remarkable physical and chemical properties, and high specific surface area. MOFs are self-assembling metal ions or clusters with organic linkers. Metals are used as dowel pins to build two-dimensional or three-dimensional frameworks, and organic linkers serve as carriers. Modern research has mainly focused on designing MOFs-based materials with improved adsorption and separation properties. In this review, for the first time, an in-depth look at the use of MOFs nanofiber materials for HMIs removal applications is provided. This review will focus on the synthesis, properties, and recent advances and provide an understanding of the opportunities and challenges that will arise in the synthesis of future MOFs-nanofiber composites in this area. MOFs decorated on nanofibers possess rapid adsorption kinetics, a high adsorption capacity, excellent selectivity, and good reusability. In addition, the substantial adsorption capacities are mainly due to interactions between the target ions and functional binding groups on the MOFs-nanofiber composites and the highly ordered porous structure.